Pengembangan Sistem Informasi Pengelolaan dan Peramalan Barang Menggunakan Metode Weighted Moving Average di Toko Welfa Sijunjung - Muhammad Prabu Sutomo; Agi Putra Kharisma; Candra Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The process of managing the goods at Welfa Sijunjung Store is everything that is related to many things. Process of managing goods at Welfa Stores include the sale of goods, data collection of goods, incoming goods, outgoing goods, and recording of consumer cash supplies. There are problems that are ineffective and inefficient in the process of managing goods at Welfa Sijunjung Shop because the management process is still carried out manually and conventionally. Data storage of incoming and outgoing goods, storing consumer cashbase data that is stored manually and only uses paper makes it very possible to lose or damage. The stock of goods in Welfa Stores is often left over and requires good forecasting of goods so that there is no accumulation of stock. In this study, a management and forecasting system for goods was developed which is expected to be able to handle the problems of managing goods at the Welfa Sijunjung Store. The system must be able to run on multiple browsers because this system is made web-based. In its development, this system uses the development of the waterfall model. In this study there are several stages, the first is to identify the problem, then study the literature, then carry out requirements engineering, design, implement, after implementation will be tested, after completion of testing the next stage is drawing conclusions and also suggestions. In this study there is a Weighted Moving Average method to forecast the stock of goods to be sold in the next period. This system was tested using unit testing and got valid results in 3 test cases, for validation testing getting valid results for 21 functionals tested, testing methods getting MAD results of 2.3, MSE of 7.9 and MAPE of 20.1 %.